2008
DOI: 10.1002/app.28266
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of polycaprolactone–clay nanocomposites

Abstract: ABSTRACT:The isothermal crystallization process of polycaprolactone/clay nanocomposites was studied at several temperatures. The effects of the clay type (modified and unmodified) and clay content were analyzed. Bulk crystallization was studied with differential scanning calorimetry and modeled with Avrami's equation. The reinforcement phase lowered the time at which the first crystal nucleus appeared (i.e., the induction time) and fastened the global crystallization rate in comparison with that of neat polyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 37 publications
(45 reference statements)
2
28
0
Order By: Relevance
“…18.8); Avrami rate constant increased by two orders of magnitude, resembling the effect previously observed in PCL filled with carbon nanotubes [93] and nanoclay [94]. 18.8); Avrami rate constant increased by two orders of magnitude, resembling the effect previously observed in PCL filled with carbon nanotubes [93] and nanoclay [94].…”
Section: Polycaprolactone/cellulose Nanocompositessupporting
confidence: 71%
“…18.8); Avrami rate constant increased by two orders of magnitude, resembling the effect previously observed in PCL filled with carbon nanotubes [93] and nanoclay [94]. 18.8); Avrami rate constant increased by two orders of magnitude, resembling the effect previously observed in PCL filled with carbon nanotubes [93] and nanoclay [94].…”
Section: Polycaprolactone/cellulose Nanocompositessupporting
confidence: 71%
“…This work showed that the very well dispersed organoclay platelets acted as nucleating agents in PCL matrix, reducing the crystallization half-time t 1/2 . In the same way, Ludueña et al [56] have shown the correlation between polymer/clay compatibility-i.e. the dispersion state-and the crystallization rate.…”
Section: Crystalline Behavior Of Pcl/clay Nanocompositesmentioning
confidence: 71%
“…The melt intercalation technique has also been applied in the processing of PCL/ clay nanocomposites; 88,94,[101][102][103][104][105][106][107]109 these yielded mostly intercalated or intercalated/ exfoliated structures. Overall, conventional microcomposites were realized when using pristine clay, MMT-Na + , whereas organically modifi ed microcomposites 6.16 Synthesis of octa(2-hydroxyethyl dimethylaminopropyl) polyhedral oligomeric silsesquioxane (POSS) (adapted with kind permission from Hossain et al 121 ).…”
Section: Clay-containing Nanocomposites Of Pclmentioning
confidence: 99%